KAJIAN FILOSOFIS KONSEP SIVAISTIS DALAM TEKS LONTAR PAMATELU BHATARA - I Wayan Gata (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The Lontar Pamatelu Bhatara Text is one of the text found in the Museum Gedong Kertya Singaraja, with the original petal number III b.1580/43, in the form of the text that was translated by Gede Dangin On 5 February 1940. While the origional Lontar Pamatelu Bhatara in Pegesengan Lombok which is the property of Ketut Rumiasta, and finally the script entered at the Museum Gedong Kertya Singaraja on 2 February 1939.Â Lontar Pamatelu Bhataraâ€™s text is structured through direct exposure to the concept of God that is about the essence of the concepts of Siva, Sada Siva and Parama Siva. This shows that teh text of Lontar Pamatelu Bhatara adheres to Sivaistis understanding whisch is related to the socio religious Hindu community in Bali. In the Lontar described Bhatara as if having three different forms, but in fact he is only one. In addition, in this ejection, the process of creation and fusion, namely the process of birth, life and death (Stiti-Utpeti-Pralina), is explained about the process of the union of atma with Parama Atma (Brahman) which can only be achieved when a person can be separated from bonds good karma and bad karma. This can only be done by diligently carrying out spiritual dicipline which is strongly influenced by oneâ€™s level of jnana or level of knowledge.